2020
DOI: 10.1155/2020/8019467
|View full text |Cite
|
Sign up to set email alerts
|

Depression of lncRNA NEAT1 Antagonizes LPS-Evoked Acute Injury and Inflammatory Response in Alveolar Epithelial Cells via HMGB1-RAGE Signaling

Abstract: Sepsis-evoked acute lung injury (ALI) and its extreme manifestation, acute respiratory distress syndrome (ARDS), constitute a major cause of mortality in intensive care units. High levels of the long noncoding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) have been positively correlated with increased severity and unfavorable prognoses in patients with sepsis. Nevertheless, the function and molecular mechanism of NEAT1 in ALI remain elusive. In the current study, high levels of NEAT1 were confirmed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 28 publications
(42 reference statements)
0
65
0
Order By: Relevance
“…LncRNA NEAT1 is reported to be a critical regulator is the progression of sepsis. According to previous studies, the down‐regulation of lncRNA NEAT1 decreases several pro‐inflammatory cytokines by modulating let‐7a/TRL4 pathway, high‐mobility group box 1/receptors for advanced glycation end product (HMGB1/RAGE) pathway and NF‐κB pathway in sepsis cell model 11,13 . Meanwhile, inhibition of lncRNA NEAT1 alleviates cell apoptosis but promotes proliferation in sepsis‐evoked acute lung injury cell model 13 ; interestingly, similar results are also reported in sepsis‐induced acute kidney injury, myocardial injury, and brain injury cell models 10‐12 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…LncRNA NEAT1 is reported to be a critical regulator is the progression of sepsis. According to previous studies, the down‐regulation of lncRNA NEAT1 decreases several pro‐inflammatory cytokines by modulating let‐7a/TRL4 pathway, high‐mobility group box 1/receptors for advanced glycation end product (HMGB1/RAGE) pathway and NF‐κB pathway in sepsis cell model 11,13 . Meanwhile, inhibition of lncRNA NEAT1 alleviates cell apoptosis but promotes proliferation in sepsis‐evoked acute lung injury cell model 13 ; interestingly, similar results are also reported in sepsis‐induced acute kidney injury, myocardial injury, and brain injury cell models 10‐12 .…”
Section: Discussionmentioning
confidence: 93%
“…Possible explanations might be that (a) lncRNA NEAT1 high expression might modulate several signaling pathways (including the NF-κB pathway and HMGB1/RAGE pathway 11,13 ) to exacerbate inflammation and organ injury when the host was infected and (b) decreased promote inflammation and to suppress the clearance of invading microbiome of the immune system. 19,25 ARDS is one of the common complications of sepsis that might worsen the prognosis of sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that knockdown of NEAT1 suppressed apoptosis, as evidenced by lower caspase-3 and caspase-9 activities, while increasing cell viability, migration, and invasion. Similarly, NEAT1 depletion enhanced the viability and reduced apoptosis and caspase-3/9 activities in alveolar epithelial cells challenged with lipopolysaccharide [ 19 ]. Moreover, NEAT1 potentiated the angiogenesis and survival of brain microvascular endothelial cells exposed to oxygen-glucose deprivation by targeting miR-377 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs were able to regulate varied genes expressed in cells and tissues [6]. It is reported that multiple lncRNAs have contribute to the progress of ALI, for example, high levels of the lncRNAs nuclear paraspeckle assembly transcript 1 (NEAT1) aggravated the progression of ALI via HMGB1/RAGE signaling, increased metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was positively correlated with increased severity and unfavorable prognoses via TSC2-mTOR and NF-κB signaling pathways [7] [8][9] [10]. Long noncoding RNA taurine up-regulated gene 1 (TUG1) targeted to miR-34b-5p and activated GRB2 associated binding protein 1 (GAB1), which showed a reducing pulmonary injury in ALI mice [11].…”
Section: Introductionmentioning
confidence: 99%